ASSESSMENT OF HAND GRIP STRENGTH BETWEEN NATIONAL LEVEL BASKETBALL AND NETBALL PLAYERS - Mr. Rohit Kumar , Dr Reeta Devi , Mr. Sunil kumar , Mr. Kuljit Singh, Harpreet kaur (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
In this investigation university competitors, who used to participate in between National Basktball and Netball players was chosen as subjects to determine hand grip strength. the specialist chose thirty (50) players from Senior national The age gathering of the subjects was run from (18-30) a long time. To determine handgrip strength among Senior National Basketball and Netball player, a Dynamometer was utilized to assess the downturn, tension and worry of the subjects. The current examination, uncovers that Left hand grip and right hand grip strength were unprecedented among National level players where mean score (M= 47.15) with standard deviation (SD= 6.86) of Basketball players and of Netball players mean score (M=46.62) with standard deviation (SD= 5.81) in case of right grip strength were determined. There were no positive differences in the dominant and non-dominant hand grip strength of Basketball and Netball senior national level players.